Successful Surgical Treatment of Congenital Aortopulmonary Window in an Adult Patient - Alessandro Giamberti; Raul Abella; Eduardo Consuegra Llapur; Abdallah Raweh; Silvia Cirri; Alessandro Frigiola (Case Reports in Cardiology)
Congenital aortopulmonary window is a rare inborn cardiac malformation that should be surgically treated as soon as the diagnosis is made usually during infancy. We report a successful surgical treatment of a 23-year-old male patient with a big type III aortopulmonary window.